Boron-aluminum paste, N-type IBC battery and preparation method of N-type IBC battery

By using boron and aluminum paste of aluminum powder, silver powder, boron powder, glass powder and organic additives in N-type IBC batteries for high-temperature sintering and laser doping, the complex process and side effects of the p-type doping region of existing N-type IBC batteries are solved. The problem of improving the photoelectric conversion efficiency and contact performance of the battery.

CN119230158AActive Publication Date: 2024-12-31DAS SOLAR CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310802710.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

The formation method of the p-type doped region of the existing N-type IBC battery is complex in technology and has many side effects, which affects the photoelectric conversion efficiency of the battery.

Method used

Using a boron aluminum paste, including aluminum powder, silver powder, boron powder, glass powder, organic binder and organic additive, the p-type doping region in N-type IBC cells is formed through high-temperature sintering and laser doping, avoiding the traditional Side effects of doping method of tube boron source.

Benefits of technology

It improves the photoelectric conversion efficiency of the battery, reduces the contact resistivity between the positive gate and the battery, avoids process complexity and side effects, and improves the filling and efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230158A_ABST
    Figure CN119230158A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides boron-aluminum paste, an N-type IBC battery and a preparation method thereof, the boron-aluminum paste provided by the embodiment of the invention is used for laser doping to form a p-type doped region in the N-type IBC battery, and the boron-aluminum paste comprises the following components: aluminum powder, silver powder, boron powder, glass powder, an organic binder and an organic additive. Boron powder is added into aluminum paste, the aluminum paste is directly printed on an n-type raw silicon region, and then high-temperature sintering and laser doping are performed, so that high-concentration boron doping can be performed on the n-type raw silicon region to form a p-type doped region, side effects caused by a traditional tubular boron source doping mode are avoided, the conversion efficiency of a battery is ensured, and the service life of the battery is prolonged. Therefore, the problem that the photoelectric conversion efficiency of the cell is easily affected due to the complex forming process and more side effects of the p-type doped region of the existing N-type IBC cell is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of crystalline silicon solar cell manufacturing, and in particular to a boron aluminum paste, an N-type IBC cell and a preparation method thereof. Background Art

[0002] The interdigitated back contact (IBC) battery is a new type of battery in which the contact electrodes of the P / N junction, substrate and emitter region are made in an interdigitated shape on the back of the battery. Its core technology is to prepare high-quality p-regions and n-regions arranged in an interdigitated shape on the back of the battery.

[0003] The p-type doping region of the existing N-type IBC cell is obtained by boron diffusion treatment, which has a complex process and many side effects, and is likely to affect the photoelectric conversion efficiency of the cell. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a boron aluminum paste, an N-type IBC battery and a preparation method thereof, so as to solve the problem that the formation method of the p-type doping region of the existing N-type IBC battery is complex in process and has many side effects, which easily affects the photoelectric conversion efficiency of the battery.

[0005] In order to solve the above problems, the present invention is achieved through the following technical solutions:

[0006] The present invention provides a boron aluminum paste, which is used for laser doping to form a p-type doping region in an N-type IBC battery. The components constituting the boron aluminum paste include aluminum powder, silver powder, boron powder, glass powder, organic adhesive and organic additives.

[0007] Furthermore, in the boron-aluminum paste, the mass percentage of the organic additive is 0.3-0.8%; the mass percentage of the boron powder is 0.5-1%; the mass percentage of the aluminum powder is 74-80%; the mass percentage of the organic binder is 16.7-24.2%; and the mass percentage of the glass powder is 1-1.5%.

[0008] Furthermore, in the boron-aluminum paste, the boron powder includes elemental boron and / or boron-aluminum alloy.

[0009] Furthermore, in the boron aluminum paste, the organic additive includes two or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, lauryl phosphate, silicone oil, dibasic acid ester, and lauryl alcohol phosphate.

[0010] Furthermore, in the boron aluminum paste, the aluminum powder includes 85-90% by mass of micron spherical aluminum powder and 10-15% by mass of nano spherical aluminum powder.

[0011] Furthermore, in the boron aluminum paste, the organic binder includes a high molecular polymer resin and an organic solvent;

[0012] The mass fraction of the high molecular weight polymer in the organic binder is 6 to 10%;

[0013] The mass fraction of the organic solvent in the organic binder is 90-94%.

[0014] Furthermore, in the boron aluminum paste, the organic solvent is at least five of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.

[0015] Furthermore, in the boron-aluminum paste, the glass powder includes Bi2O3 with a mass fraction of 15-25%, Al2O3 with a mass fraction of 6-10%, Pb2O5 with a mass fraction of 10-15%, ZnO with a mass fraction of 12-29%, Sb2O5 with a mass fraction of 15-25%, V2O5 with a mass fraction of 6-10%, TiO2 with a mass fraction of 9-25%, and BaO with a mass fraction of 10-20%.

[0016] Furthermore, in the boron aluminum paste, the boron powder is micron-grade boron powder.

[0017] The present invention also proposes a method for preparing a boron aluminum paste for laser doping to form a p-type doping region in an N-type IBC battery, which comprises:

[0018] mixing aluminum powder, boron powder, an organic binder and glass powder to obtain a mixture;

[0019] After grinding the mixture, an organic additive is added to obtain a boron-aluminum paste for laser doping to form a p-type doping region in an N-type IBC cell.

[0020] The present invention also proposes an N-type IBC battery, wherein the back side of the N-type IBC battery includes an n-type doped region and a p-type doped region arranged in an interdigitated manner, and the p-type doped region is prepared by printing and sintering the above-mentioned boron aluminum paste and then laser doping.

[0021] Compared with the prior art, the embodiments of the present invention have the following advantages:

[0022] In the embodiment of the present invention, the boron aluminum paste provided comprises aluminum powder, silver powder, boron powder, glass powder, organic binder and organic additive. By adding boron powder to the aluminum paste, directly printing it on the n-type original silicon area and then performing high-temperature sintering and laser doping, the n-type original silicon area can be doped with high-concentration boron to form a p-type doped area, avoiding the side effects of the doping method using the traditional tubular boron source, ensuring the conversion efficiency of the battery, and thus solving the problem that the formation method of the p-type doped area of ​​the existing N-type IBC battery is complicated in process and has many side effects, which easily affects the photoelectric conversion efficiency of the battery.

[0023] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a flow chart of the method for preparing boron aluminum paste provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0026] The applicant of the present invention has found that the current N-type IBC technology route is simply to prepare high-quality P and N regions with interdigitated spacing on the back of the battery. It uses tubular boron diffusion on the original silicon wafer to form the P+ region. Not only is the process complicated and costly, but the emitter contact resistance of the p-type doped region formed is large, resulting in a low open circuit voltage value of the battery and poor photoelectric conversion efficiency of the battery.

[0027] In order to solve the above problems, an embodiment of the present invention provides a boron aluminum paste for laser doping to form a p-type doped region in an N-type IBC battery. The components constituting the boron aluminum paste include aluminum powder, silver powder, boron powder, glass powder, organic binder and organic additives.

[0028] Among them, aluminum powder is the main component, and aluminum powder mainly replaces the P+ emitter of the battery, while boron powder can diffuse into the silicon for heavy doping during high-temperature sintering, which is beneficial to improve the contact performance of the slurry, reduce the reaction contact surface between aluminum and silicon, and reduce the contact resistivity between the positive electrode grid and the battery, thereby improving the filling of the battery and the efficiency of the battery;

[0029] Among them, glass powder is an inorganic adhesive, which will melt into liquid under high temperature conditions and condense when cooled to play a bonding role; organic adhesive can ensure the overall bonding effect; organic additives can reduce the overall viscosity of silver paste.

[0030] Therefore, the boron-aluminum paste provided in the embodiment of the present invention can form a high-concentration p-type doped region after sintering and laser doping treatment, which has better contact with the battery cell itself and smaller series resistance than traditional aluminum paste, thereby avoiding the side effects brought about by the doping method of the traditional tubular boron source, that is, ensuring the conversion efficiency of the battery, and solving the problem that the formation method of the p-type doped region of the existing N-type IBC battery is complex and has many side effects, which easily affects the photoelectric conversion efficiency of the battery.

[0031] Optionally, in one embodiment, in the above boron aluminum paste, the mass percentage of organic additives is 0.3-0.8%; the mass percentage of boron powder is 0.5-1%; the mass percentage of aluminum powder is 74-80%; the mass percentage of organic binder is 16.7-24.2%; the mass percentage of glass powder is 1-1.5%. In the boron aluminum paste provided by the embodiment of the present invention, the aluminum content is relatively low. When forming aluminum silicon alloy, the proportion of aluminum in aluminum silicon alloy is relatively small, so during the cooling process, there will be no excess aluminum to diffuse into the PN junction area and form a metal composite area; at the same time, the boron content is relatively high, and the application of sintering combined with laser doping can form a high-concentration doped p-type doping area.

[0032] For example, in the boron aluminum paste, the mass fractions of the organic additive, boron powder, aluminum powder, organic binder and glass powder are 0.5%, 0.5%, 76%, 21.5% and 1.5% respectively.

[0033] For example, in the boron aluminum paste, the mass fractions of the organic additive, boron powder, aluminum powder, organic binder and glass powder are 0.8%, 1%, 80%, 16.7% and 1.5% respectively.

[0034] For example, in the boron aluminum paste, the mass fractions of the organic additive, boron powder, aluminum powder, organic binder and glass powder are 0.3%, 0.5%, 74%, 24.2% and 1% respectively.

[0035] For example, in the boron aluminum paste, the mass fractions of the organic additive, boron powder, aluminum powder, organic binder and glass powder are 0.5%, 0.8%, 76%, 21.5% and 1.2% respectively.

[0036] Optionally, in one embodiment, the boron powder comprises elemental boron.

[0037] Optionally, in a specific embodiment, the boron powder includes micron-sized elemental boron. By adding the micron-sized elemental boron, the boron powder can quickly diffuse into the silicon for heavy doping during high-temperature sintering, which is beneficial to improving the contact performance of the slurry.

[0038] Optionally, in a specific embodiment, the boron powder is a micron-grade boron powder with a purity of 2 9s.

[0039] Optionally, in another embodiment, the above includes boron aluminum alloy. By adding the micron-sized boron aluminum alloy powder, the boron aluminum paste can quickly form a good alloy with silicon under a lower sintering temperature condition, thereby reducing the contact resistivity between the front boron aluminum fine gate and the n-type original silicon wafer.

[0040] Optionally, in one embodiment, the aluminum powder includes 85-90% by mass of micron-sized spherical aluminum powder and 10-15% by mass of nano-sized spherical aluminum powder. Since there are gaps between the micron-sized aluminum powders, the nano-sized spherical aluminum powder can just fill and penetrate into the gaps between the micron-sized aluminum powders.

[0041] Optionally, in a specific embodiment, the aluminum powder includes micron-sized spherical aluminum powder with a purity of 3 9s, a mass fraction of 85-90%, and a D50 of 5-6 μm, and nano-sized spherical aluminum powder with a purity of 3 9s, a mass fraction of 10-15%, and a D50 of 7-9 nm.

[0042] Optionally, in one embodiment, the above-mentioned organic additives include two or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, lauryl phosphate, silicone oil, dibasic acid ester, lauryl alcohol phosphate, Digo 655, BYK110, and BYK105.

[0043] In the boron aluminum paste provided in the embodiment of the present invention, the above-mentioned organic binder includes a polymer resin and an organic solvent; wherein the polymer resin is dissolved in the organic solvent, so that the organic solvent can be used as an organic binder, that is, the paste plays a role of bonding powder after drying.

[0044] Optionally, in one embodiment, the mass fraction of the high molecular weight polymer in the organic binder is 10-15%; the mass fraction of the organic solvent in the organic binder is 85-90%.

[0045] Optionally, in one embodiment, the high molecular weight polymer is one or more of ethyl cellulose-N20, ethyl cellulose N-50, and ethyl cellulose-N100;

[0046] The organic solvent includes at least five of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.

[0047] Optionally, in one embodiment, the glass powder includes, by mass, 15-25% Bi2O3, 6-10% Al2O3, 10-15% Pb2O5, 12-29% ZnO, 15-25% Sb2O5, 6-10% V2O5, 9-25% TiO2, and 10-20% BaO, and the D50 of the glass powder is 1.5-2μm. If D50 is less than 1.5μm, the glass activity is too large, and if D50 is greater than 2μm, the glass activity is too small.

[0048] Among them, Bi2O3 is the main network structure, ZnO can break the network structure and promote glass crystallization, Sb2O5 is used to clarify and uniform the glass liquid; Al2O3 can adjust the stability of the glass and increase the viscosity; Pb2O5 reacts with silicon nitride to generate lead, nitrogen and silicon dioxide; V2O5 and TiO2 can assist Pb2O5 and silicon nitride in the reaction; BaO is used for local crystallization.

[0049] For example, the glass powder includes, by mass, 15% Bi2O3, 10% Al2O3, 10% Pb2O5, 15% ZnO, 15% Sb2O5, 15% V2O5, 15% TiO2, and 5% BaO.

[0050] For example, the glass powder includes, by mass, 25% Bi2O3, 6% Al2O3, 10% Pb2O5, 5% ZnO, 15% Sb2O5, 15% V2O5, 15% TiO2, and 9% BaO.

[0051] For example, the glass powder includes, by mass, 22% Bi2O3, 6% Al2O3, 12% Pb2O5, 10% ZnO, 18% Sb2O5, 7% V2O5, 15% TiO2, and 10% BaO.

[0052] The embodiment of the present invention also provides a method for preparing a boron aluminum paste for laser doping to form a p-type doping region in an N-type IBC battery, wherein Figure 1 As shown, it includes steps 101 to 102:

[0053] Step 101, mixing aluminum powder, boron powder, organic binder and glass powder to obtain a mixture;

[0054] Step 102: grind the mixture, add an organic additive, and obtain a boron-aluminum paste for laser doping to form a p-type doping region in an N-type IBC cell.

[0055] In the above step 101, 74-80% of aluminum powder, 0.5-1% of boron powder, 16.7-24.2% of organic binder, and 1-1.5% of glass powder accounting for the total mass of the raw materials are weighed and mixed, and dispersed by a disperser to obtain the above mixture.

[0056] Optionally, in one embodiment, in the above step 101, the organic binder and boron powder are first mixed and dispersed using a disperser, and then aluminum powder and glass powder are added, dispersed again using a disperser, and then ground to obtain the above mixture.

[0057] In the above step 102, the above mixture is ground and then an organic additive accounting for 0.3-0.8% of the total mass of the raw materials is added, and after high-speed dispersion, a boron aluminum paste for laser doping to form a p-type doping region in an N-type IBC battery is obtained.

[0058] In the embodiment of the present invention, by adding boron powder to the aluminum paste, directly printing it on the n-type original silicon area and then performing high-temperature sintering and laser doping, the n-type original silicon area can be doped with high-concentration boron to form a p-type doped area, thereby avoiding the side effects caused by the doping method of the traditional tubular boron source, ensuring the conversion efficiency of the battery, and thus solving the problem that the formation method of the p-type doped area of ​​the existing N-type IBC battery is complex and has many side effects, which easily affects the photoelectric conversion efficiency of the battery.

[0059] Optionally, in the preparation method provided in the embodiment of the present invention, the boron powder is micron-sized boron aluminum alloy and / or micron-sized elemental boron. Micron-sized boron aluminum alloy and micron-sized elemental boron have the characteristics of high tap density, low oxygen content and high activity. By adding the micron-sized boron aluminum alloy powder and / or micron-sized elemental boron, the silver aluminum paste can quickly form a good alloy with silicon under low sintering temperature conditions, thereby reducing the contact resistivity between the front silver aluminum fine grid and the battery.

[0060] Optionally, in the preparation method provided in an embodiment of the present invention, the organic additive includes two or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, lauryl phosphate, silicone oil, dibasic acid ester, and lauryl alcohol phosphate.

[0061] Optionally, in the preparation method provided in the embodiment of the present invention, the aluminum powder includes 85-90% by mass of micron spherical aluminum powder and 10-15% by mass of nano spherical aluminum powder.

[0062] Optionally, in the preparation method provided in the embodiment of the present invention, the organic binder comprises a high molecular polymer resin and an organic solvent;

[0063] The mass fraction of the high molecular weight polymer in the organic binder is 6 to 10%;

[0064] The mass fraction of the organic solvent in the organic binder is 90-94%.

[0065] Optionally, in the preparation method provided in an embodiment of the present invention, the organic solvent is at least five of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.

[0066] Optionally, in the preparation method provided in an embodiment of the present invention, the glass powder includes Bi2O3 with a mass fraction of 15-25%, Al2O3 with a mass fraction of 6-10%, Pb2O5 with a mass fraction of 10-15%, ZnO with a mass fraction of 12-23%, Sb2O5 with a mass fraction of 15-25%, V2O5 with a mass fraction of 6-10%, TiO2 with a mass fraction of 15-25%, and BaO with a mass fraction of 10-20%.

[0067] The present invention also proposes an N-type IBC battery, wherein the back side of the N-type IBC battery includes an n-type doped region and a p-type doped region arranged in an interdigitated manner, and the p-type doped region is prepared by laser doping after printing and sintering the above-mentioned boron aluminum paste.

[0068] The steps of manufacturing an N-type IBC battery using the boron aluminum paste provided in the embodiment of the present invention are as follows:

[0069] (1) After sequentially forming a silicon oxide layer and a phosphorus-doped polysilicon layer on the back of an N-type silicon wafer, laser grooving is performed on the back of the silicon wafer to form an n-type doped region and an n-type original silicon region arranged in an interdigitated manner;

[0070] (2) printing a boron-aluminum slurry on a first region within the n-type original silicon region and performing high-temperature sintering to form a boron-aluminum coating, and then performing laser doping treatment on the first region;

[0071] (3) After laser doping treatment, a passivation film layer and an anti-reflection film layer are formed on both sides of the silicon wafer;

[0072] (4) After forming the anti-reflection film layer, a positive electrode grid line in contact with the first region and a negative electrode grid line in contact with the n-type doped region are formed on the back side of the silicon wafer to produce an N-type IBC battery.

[0073] The present invention is described in detail below by way of examples.

[0074] Example 1

[0075] (1) providing a boron aluminum paste a1: the boron aluminum paste a1 is composed of 0.5 parts of an organic additive, 0.5 parts of boron powder, 76 parts of aluminum powder, 21.5 parts of an organic binder and 1.5 parts of glass powder, by weight;

[0076] Among them, the above-mentioned organic additives are lauryl alcohol phosphate and BYK110; the boron powder is micron-grade elemental boron with a purity of 2 nines; the aluminum powder includes micron-grade spherical aluminum powder with a purity of 3 nines and a mass fraction of 88%, and nano-spherical aluminum powder with a purity of 3 nines and a mass fraction of 12%; the organic binder includes ethyl cellulose-N100 with a mass fraction of 6% and an organic solvent with a mass fraction of 94%, and the organic solvent is composed of benzyl alcohol, pine oil, butyl carbitol, butyl carbitol acetate and Span 85; the glass powder is obtained by sintering and crushing 17% Bi2O3, 8% Al2O3, 12% Pb2O5, 15% ZnO, 20% Sb2O5, 6% V2O5, 12% TiO2, and 10% BaO with a mass percentage, and its D50 is 1.5-2μm.

[0077] (2) The above-mentioned boron aluminum paste is screen-printed on a single crystal N-type silicon wafer with a size of 182mm×182mm through a 360-mesh screen to form an aluminum fine grid, which is then sintered in a sintering furnace with a peak sintering temperature of 768°C. After sintering, the aluminum fine grid is punched with a low-power laser, and the aluminum fine grid is doped. After being cleaned with hydrochloric acid, the square resistance is tested to be 105Ω and the ECV concentration is tested to be 9E18, which meets the boron diffusion requirements.

[0078] Example 2

[0079] (1) providing a boron aluminum paste a2: the boron aluminum paste a2 is composed of 0.8 parts of an organic additive, 1 part of boron powder, 80 parts of aluminum powder, 16.7 parts of an organic binder and 1.5 parts of glass powder, by weight;

[0080] Among them, the above-mentioned organic additives are lauryl alcohol phosphate and BYK105; the boron powder is micron-grade elemental boron with a purity of 2 nines; the aluminum powder includes micron-grade spherical aluminum powder with a purity of 3 nines and a mass fraction of 88%, and nano-spherical aluminum powder with a purity of 3 nines and a mass fraction of 12%; the organic binder includes ethyl cellulose-N100 with a mass fraction of 6% and an organic solvent with a mass fraction of 94%, and the organic solvent is composed of benzyl alcohol, pine oil, butyl carbitol, butyl carbitol acetate and Span 85; the glass powder is obtained by sintering and crushing 17% Bi2O3, 8% Al2O3, 12% Pb2O5, 15% ZnO, 20% Sb2O5, 6% V2O5, 12% TiO2, and 10% BaO with a mass percentage, and its D50 is 1.5-2μm.

[0081] (2) The above-mentioned boron aluminum paste is screen-printed on a single crystal N-type silicon wafer with a size of 182mm×182mm through a 360-mesh screen to form an aluminum fine grid, which is then sintered in a sintering furnace with a peak sintering temperature of 772°C. After sintering, the aluminum fine grid is punched with a low-power laser, and the aluminum fine grid is doped. After being cleaned with hydrochloric acid, the square resistance is tested to be 95Ω and the ECV concentration is tested to be 1.05E19, which meets the boron diffusion requirements.

[0082] Example 3

[0083] (1) providing a boron aluminum paste a3: the boron aluminum paste a3 is composed of 0.3 parts of an organic additive, 0.5 parts of boron powder, 74 parts of aluminum powder, 24.2 parts of an organic binder and 1 part of glass powder, by weight;

[0084] Among them, the above-mentioned organic additives are lauryl alcohol phosphate and BYK110; the boron powder is boron aluminum alloy; the aluminum powder includes micron-grade spherical aluminum powder with a purity of 3 9s and a mass fraction of 88%, and nano-spherical aluminum powder with a purity of 3 9s and a mass fraction of 12%; the organic binder includes ethyl cellulose-N100 with a mass fraction of 6% and an organic solvent with a mass fraction of 94%, and the organic solvent is composed of benzyl alcohol, pine oil, butyl carbitol, butyl carbitol acetate and Span 85; the glass powder is obtained by sintering and crushing 17% Bi2O3, 8% Al2O3, 12% Pb2O5, 15% ZnO, 20% Sb2O5, 6% V2O5, 12% TiO2, and 10% BaO with a mass percentage, and its D50 is 1.5-2μm.

[0085] (2) The above boron aluminum paste is screen printed on a single crystal N-type silicon wafer with a size of 182mm×182mm through a 360-mesh screen to form an aluminum fine grid, which is then put into a sintering furnace for sintering. The peak sintering temperature is 772°C. After sintering, the aluminum fine grid is punched with a low-power laser, and the aluminum fine grid is doped. After cleaning with hydrochloric acid, the square resistance is tested to be 40Ω and the ECV concentration is tested to be 1E19, which meets the boron diffusion requirements.

[0086] Example 4

[0087] (1) providing boron aluminum paste a4: the boron aluminum paste a4 is composed of 0.5 parts of organic additives, 0.8 parts of boron powder, 76 parts of aluminum powder, 21.5 parts of organic binder and 1.2 parts of glass powder by weight;

[0088] Among them, the above-mentioned organic additives are lauryl alcohol phosphate and BYK110; the boron powder is micron-grade elemental boron with a purity of 2 nines; the aluminum powder includes micron-grade spherical aluminum powder with a purity of 3 nines and a mass fraction of 88%, and nano-spherical aluminum powder with a purity of 3 nines and a mass fraction of 12%; the organic binder includes ethyl cellulose-N100 with a mass fraction of 6% and an organic solvent with a mass fraction of 94%, and the organic solvent is composed of benzyl alcohol, pine oil, butyl carbitol, butyl carbitol acetate and Span 85; the glass powder is obtained by sintering and crushing 17% Bi2O3, 8% Al2O3, 12% Pb2O5, 15% ZnO, 20% Sb2O5, 6% V2O5, 12% TiO2, and 10% BaO with a mass percentage, and its D50 is 1.5-2μm.

[0089] (2) The above boron aluminum paste is screen printed on a single crystal N-type silicon wafer with a size of 182mm×182mm through a 360-mesh screen to form an aluminum fine grid, which is then sintered in a sintering furnace with a peak sintering temperature of 776°C. After sintering, the aluminum fine grid is punched with a low-power laser, and the aluminum fine grid is doped. After cleaning with hydrochloric acid, the square resistance is tested to be 42Ω and the ECV concentration is tested to be 1.85E18, which meets the boron diffusion requirements.

[0090] Example 5

[0091] (1) providing boron aluminum paste a5: the boron aluminum paste a4 is composed of 0.5 parts of organic additives, 0.8 parts of boron powder, 76 parts of aluminum powder, 21.5 parts of organic binder and 1.2 parts of glass powder by weight;

[0092] Among them, the above-mentioned organic additives are lauryl alcohol phosphate and BYK110; the boron powder is micron-grade elemental boron with a purity of 2 nines; the aluminum powder includes micron-grade spherical aluminum powder with a purity of 3 nines and a mass fraction of 88%, and nano-spherical aluminum powder with a purity of 3 nines and a mass fraction of 12%; the organic binder includes ethyl cellulose-N100 with a mass fraction of 6% and an organic solvent with a mass fraction of 94%, and the organic solvent is composed of benzyl alcohol, pine oil, butyl carbitol, butyl carbitol acetate and Span 85; the glass powder is obtained by sintering and crushing 15% Bi2O3, 6% Al2O3, 10% Pb2O5, 29% ZnO, 15% Sb2O5, 6% V2O5, 9% TiO2, and 10% BaO with a mass percentage, and its D50 is 1.5-2μm.

[0093] (2) The above boron aluminum paste is screen printed on a single crystal N-type silicon wafer with a size of 182mm×182mm through a 360-mesh screen to form an aluminum fine grid, which is then sintered in a sintering furnace with a peak sintering temperature of 774°C. After sintering, the aluminum fine grid is punched with a low-power laser, and the aluminum fine grid is doped. After cleaning with hydrochloric acid, the square resistance is tested to be 42Ω and the ECV concentration is tested to be 1.1E19, which meets the boron diffusion requirements.

[0094] It can be seen from Examples 1 to 5 that by printing the boron aluminum paste in the embodiments of the present invention on the n-type original silicon area and then performing high-temperature sintering and laser doping, the n-type original silicon area can be doped with high concentration of boron to form a p-type doped area.

[0095] In summary, in this embodiment, by adding boron powder to the aluminum paste, directly printing it on the n-type original silicon area and then performing high-temperature sintering and laser doping, the n-type original silicon area can be doped with high-concentration boron to form a p-type doped area, thereby avoiding the side effects caused by the doping method of the traditional tubular boron source, ensuring the conversion efficiency of the battery, and thus solving the problem that the formation method of the p-type doped area of ​​the existing N-type IBC battery is complex and has many side effects, which easily affects the photoelectric conversion efficiency of the battery.

[0096] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present invention.

[0097] The above is a detailed introduction to a boron aluminum paste, an N-type IBC battery and a preparation method thereof provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A boron aluminum slurry, characterized in that: The boron aluminum paste is used for laser doping to form a p-type doping region in an N-type IBC battery. The components constituting the boron aluminum paste include aluminum powder, silver powder, boron powder, glass powder, organic adhesive and organic additives.

2. The boron aluminum paste according to claim 1, characterized in that: The mass percentage of the organic additive is 0.3-0.8%; the mass percentage of the boron powder is 0.5-1%; the mass percentage of the aluminum powder is 74-80%; the mass percentage of the organic binder is 16.7-24.2%; and the mass percentage of the glass powder is 1-1.5%.

3. The boron aluminum paste according to claim 1, characterized in that: The boron powder includes elemental boron and / or boron-aluminum alloy.

4. The boron aluminum paste according to claim 1, characterized in that: The boron powder is micron-grade boron powder.

5. The boron aluminum paste according to claim 1, characterized in that: The organic additives include two or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, and lauryl alcohol phosphate.

6. The boron aluminum paste according to claim 1, characterized in that: The aluminum powder comprises 85-90% by mass of micron spherical aluminum powder and 10-15% by mass of nanometer spherical aluminum powder.

7. The boron aluminum paste according to claim 1, characterized in that: The organic binder includes a high molecular polymer resin and an organic solvent; The mass fraction of the high molecular weight polymer in the organic binder is 6 to 10%; The mass fraction of the organic solvent in the organic binder is 90-94%.

8. The boron aluminum paste according to claim 1, characterized in that: The organic solvent is at least five of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.

9. The boron aluminum paste according to claim 1, characterized in that: The glass powder includes Bi2O3 with a mass fraction of 15-25%, Al2O3 with a mass fraction of 6-10%, Pb2O5 with a mass fraction of 10-15%, ZnO with a mass fraction of 12-29%, Sb2O5 with a mass fraction of 15-25%, V2O5 with a mass fraction of 6-10%, TiO2 with a mass fraction of 9-25%, and BaO with a mass fraction of 10-20%.

10. An N-type IBC battery, characterized in that: The back side of the N-type IBC battery comprises an n-type doped region and a p-type doped region arranged in an interdigitated manner, and the p-type doped region is prepared by printing and sintering the boron aluminum paste described in any one of claims 1 to 9 and then laser doping.

Citation Information

Patent Citations

  • Preparation method of local boron laser doped back passivation solar cell

    CN112164735A

  • N-type high-efficiency battery front silver-aluminum paste

    CN112489851A

  • N-TOPCon front silver-aluminum paste, preparation method thereof and N-TOPCon battery

    CN115705933A

  • IBC battery aluminum paste, IBC battery and preparation method of IBC battery

    CN116344096A